Movements and Associations in the Church in the Service of Ecology - Stanisław Jaromi (Nicolaus Copernicus University in Toruń, 2011)
The paper aims at presenting theoretical foundations of the Catholics' engagement in the proecological activities as well as chosen examples of such activities undertaken in the Polish Catholic Church. Building up an integral, christian vision of creation we cannot miss on the context of modernity using our present knowledge of nature, ecological crisis or the reflection on social, cultural, economic phenomena. Many an inspiration in this work are given by the Bible, church tradition, theology, and social teachings of the Church. The contemporary Christian Gospel of life is a basis of Christian care of the creation and human environment. A good example of such engagement is the activity of the Ecological Movement of St Francisco of Assisi (Ruch Ekologiczny św. Franciszka z Asyżu - REFA) showed as a modern and evangelical example of the care of nature and the project of the Polish Council of Catholic Movements (Ogólnopolska Rada Ruchów Katolickich) forming leaders of Catholic movements and associations in Poland.